Dispersing carbon nanotubes by star-like water soluble C 60 derivatives - Li, Hongguang; Liu, Changcheng; Hao, Jingcheng; Hartnagel, Uwe; Hirsch, Andreas (Journal of Nanoscience and Nanotechnology, 2009)
The properties of three water soluble [3:3] hexakisadducts of C 1-3 are investigated both in bulk aqueous solutions and at air/water interface. 1-3 have a star-like molecular structure with six hydrophilic quarternary ammonium groups located terminally. 2 and 3 also have increasing number of ethylene oxide groups inserted into their peripheral hydrophilic arms. This molecular structure makes 1-3 highly water soluble, thus difficult to form aggregates in bulk aqueous solutions as revealed by transmission electron microscope observations. But surface tension measurements shows 1-3 still own some amphiphilic properties and can lower the surface tension of water. These unique C derivatives are also subjected to disperse carbon nanotubes (CNTs) in water for the first time. It was found the ability of each water soluble C derivative to disperse CNTs was mainly dominated by their amphiphilic feature as well as molecular weight. Copyright © 2009 American Scientific Publishers All rights reserved.